Physics Stack Exchange is a question and answer site for active researchers, academics and students of physics. It's 100% free.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I really need some assistance setting up this problem. any assistance would be a Godsend:

a uniform heavy chain of length a initially has length b hanging off of a table. The remaining part of chain a - b, is coiled on the table. Show that if the chain is released, the velocity of the chain when the last link leaves the table is $\sqrt{2g\frac{a^3 - b^3}{3a^2}}$

Okay, so this is a variable mass problem, so momentum is constantly changing:

$$F_{ext}=m(t)g=\frac{dP}{dt}= \frac{d(m(t)v(t))}{dt}=ma +v\dot{m}$$

$$mg = ma + v\dot{m}$$

Gravity acts on the mass hanging off of the table, mass can be written as a function of length, as can velocity (where $\lambda$ is the linear mass density)

$m(t) = \lambda l(t)$
$\dot{m(t)} = \lambda v(t)=\lambda \dot {l(t)}$
$v(t) = \dot {l(t)}$
$ a(t) = \ddot{l(t)}$

$$\lambda l(t)g=\lambda l(t) \ddot{l(t)} + \dot {l(t)} \lambda \dot {l(t)}$$

Assuming this all to be correct $\implies$ $0 =l(t)(g -\ddot{l(t)}) +\dot{l(t)}^2$

I've tried solved this DE, but I don't know many methods for non linear DEs.

share|cite|improve this question
Quick follow up question from a physics student - when I saw this problem, my first instinct was to use conservation of energy (compare initial and final potential energies of the chain in terms of the length hanging over). The result by doing the problem this way, however, is incorrect. Why does conservation of energy not apply? – Shivam Sarodia Dec 18 '12 at 23:57
Energy would not be easy to deal with because both kinetic and potential energy depend upon the mass, which is changing with time. Potential energy also depends upon the center of mass which is also changing in time. In theory, energy would work (lol) but it would not be practical. – Cactus BAMF Dec 19 '12 at 0:04
Are you sure there is no missing information? As Draksis points out, this is really very easy to set up in terms of energy, but the velocity then comes out to be $v=\sqrt{g(a^2-b^2) / a}$. – Jaime Dec 19 '12 at 1:38
I just threw together some quick Python code to solve Cactus BAMF's DE for a = 30 and b = 10, and the final answer (13.757104646790195) agreed well with Cactus BAMF's provided solution. The energy argument seems to therefore be flawed, but I don't see why it would be. – Shivam Sarodia Dec 19 '12 at 2:54
I gave this a shot with energy and got the same thing as Jaime... haven't checked the momentum method yet, but I'm suspecting there's something wrong there... – Kyle Oman Dec 19 '12 at 4:24
up vote 4 down vote accepted

With $\ell(t)$ as the length of the chain hanging off the table, the differential equation $$\ell(g-\ddot \ell)=\dot \ell^2 $$ from the question can be rewritten as $$y\dot y=g\ell^2 \dot\ell,$$ where $y=\ell \dot\ell$. Then, integrating over the appropriate time interval will yield a final velocity of$$v_f=\sqrt{\frac{2g}{3}\frac{a^3-b^3}{a^2}}.$$

However, the differential equation above is incorrect, as it fails to take into account the tension in the chain. The correct equation should be $$\ddot\ell=\frac{g}{a}\ell,$$ giving a final velocity of $$v_f=\sqrt{\frac{g}{a}(a^2-b^2)},$$ which is in agreement with the conservation of energy.

share|cite|improve this answer
Beat me to it :) Glad to see my intuition was correct. – Kyle Oman Dec 19 '12 at 16:18

I'll add the conservation of energy based solution just for completeness. I wrote the change in gravitational potential energy based on the picture that the piece of chain that begins on the table ends hanging vertically from a point $b$ below the table (and the rest of the chain is unchanged).

$\Delta U_g = -g\lambda\int_0^{a-b}(b+x)dx$

$\Delta K = \frac{1}{2}\lambda av^2$

Where $\lambda$ is mass per unit length of the chain.

$\frac{1}{2}av^2 = g[bx + \frac{1}{2}x^2]_0^{a-b}$

$v^2 = \frac{2g}{a}(ba-b^2+\frac{1}{2}a^2-ab+\frac{1}{2}b^2)$

$v = \sqrt{\frac{g}{a}(a^2-b^2)}$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.